2006
DOI: 10.1080/15389580600665194
|View full text |Cite
|
Sign up to set email alerts
|

Parental Supervision of Teenage Drivers in a Graduated Licensing System

Abstract: The extended learning experience required by GDL programs is a positive experience for many families. However, finding a method for helping parents achieve maximum benefits during this process will be challenging. The results also suggest that current requirements in the learner phase of most state GDL systems (six months; 30-50 hours) may be inadequate to ensure that teenagers obtain a sufficient amount of experience to begin driving safely on their own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 18 publications
0
34
1
Order By: Relevance
“…Separate research suggests that parents tend not to make the most productive use of the time spent supervising their teen's practice driving. A study using in-vehicle cameras to document the behaviors of teen drivers and parent supervisors indicated that most practice driving took place in relatively benign conditions; teens rarely drove at night, in rain, or in heavy traffic, and they tended to drive the same routes (Goodwin et al, 2006). Parents' advice to their teen drivers tended to focus on vehicle handling rather than the aforementioned higher order skills (Goodwin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Separate research suggests that parents tend not to make the most productive use of the time spent supervising their teen's practice driving. A study using in-vehicle cameras to document the behaviors of teen drivers and parent supervisors indicated that most practice driving took place in relatively benign conditions; teens rarely drove at night, in rain, or in heavy traffic, and they tended to drive the same routes (Goodwin et al, 2006). Parents' advice to their teen drivers tended to focus on vehicle handling rather than the aforementioned higher order skills (Goodwin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A study using in-vehicle cameras to document the behaviors of teen drivers and parent supervisors indicated that most practice driving took place in relatively benign conditions; teens rarely drove at night, in rain, or in heavy traffic, and they tended to drive the same routes (Goodwin et al, 2006). Parents' advice to their teen drivers tended to focus on vehicle handling rather than the aforementioned higher order skills (Goodwin et al, 2006). Taken together, these findings point to the need for parents to be better prepared for the important role of supervising their novice teen's practice driving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although parents said that the information was helpful, they used the guidance material in only a general way. The information had no effect on the amount or type of supervised driving during the learner's stage or on parental restrictions on driving after licensure (Chaudhary, Ferguson, & Herbel, 2004;Goodwin, Waller, Foss, & Margolis, 2006).…”
Section: Time To Implementmentioning
confidence: 99%
“…Current estimates indicate that the majority of US teens receive some form of professional driver education, typically 6 h of behind-the-wheel (BTW) instruction and 30 h of classroom lessons (Chaudhary et al, 2011;Curry et al, 2012). In addition, nearly all teens engage in supervised practice driving with adult family members, usually parents (Goodwin et al, 2006).…”
Section: Introductionmentioning
confidence: 97%